Short term impacts of harvesting operations on soil chemical properties in a Mediterranean oak ecosystem - Ganatsios, Harisios P. (Array, 2021)
Soil physical and chemical properties can be seriously affected by forest operations. There is a knowledge gap on this topic for oak ecosystems, which can play a significant role in the context of multiple-use forestry.The main objective of this study was to analyse forest floor and topsoil changes (0–10 cm) two years after the application of small-scale thinning (50% reduction of basal area) and clear-cut operations using mules to carry harvested material in a Northern Greece oak (Quercus frainetto Ten)ecosystem. The total amount of forest floor (O1+O2 horizons) was reduced by 37.8% in the thinned and 30.8% in the clear-cut plots compared to control plots. These large reductions are mainly due to reduction in the O2 horizon in the treated plots. Decomposition was reduced in the treated plots, possibly due to the new drier conditions. Treatments increased the soil pH but not to a significant extent. No evidence of erosion was found in the experimental plots due to the protective function of the forest floor and the use of designated mule trails. The areal extent of soil compaction was limited to only 3% of the total area mainly due to the careful planning and implementation of animal skidding. Small differences in C (%) and Ν (%) were found among control, thinned and clear-cut plots.The limiting growth factors in Mediterranean oak ecosystems are soil depth and the seasonal change of soil moisture, especially during the summer dry period. More research on the definition of the optimum thinning degree and extraction systems in similar ecosystems will be important to satisfy the need to improve soil characteristics.